Sartre's phenomenology - Reisman, David, 1963- (Continuum studies in continental philosophy., 2007)
Davis Reisman addresses central themes in 'Being and Nothingness' & compares some of Sartre's views to those of his leading contemporary from the analytic school, P.F. Strawson.